Two-dimensional gel electrophoresis image analysis via dedicated software packages - Maurer, Martin H. (2-D PAGE Map Analysis, 2016)
Analyzing two-dimensional gel electrophoretic images is supported by a number of freely and commercially available software. Although the respective program is highly specific, all the programs follow certain standardized algorithms. General steps are: (1) detecting and separating individual spots, (2) subtracting background, (3) creating a reference gel and (4) matching the spots to the reference gel, (5) modifying the reference gel, (6) normalizing the gel measurements for comparison, (7) calibrating for isoelectric point and molecular weight markers, and moreover, (8) constructing a database containing the measurement results and (9) comparing data by statistical and bioinformatic methods.
Gesehen am 13.05.2020